Health literacy and associated factors among the patients attending the medical clinics, Teaching Hospital, Jaffna - Yuvaraj, P.; Dineshkaran, K.; Jegapragash, V.; Sujanitha, V. (Faculty of Allied Health Sciences, University of Jaffna, Sri Lanka., 2025)
Introduction: Health literacy plays an important role in determining each and every person's ability to make informed health decisions and manage their health effectively. Understanding the factors associated with health literacy is essential for improving health outcomes. Objective: To identify the associated factors of health literacy among the patients attending the medical clinics Teaching Hospital Jaffna. Methodology: A hospital-based descriptive cross-sectional study was conducted among 402 patients attending the medical clinics at Teaching Hospital Jaffna in 2025 using simple random sampling. A pre-tested HLS-EU 47 standard questionnaire was used to collect the data. Ethical clearance was obtained from the Ethics Review Committee, Faculty of Medicine, University of Jaffna. Data were analyzed using SPSS 27, and the chi-square test was used to find the factors associated with health literacy. Results: - The response rate was 100%. The mean age of the participants was 63.44 years (SD=±12.282), and 68.9% (n=277) were females. According to the HLS-EU scoring scale, the findings revealed that the mean score of overall health literacy level was 65.85% (SD=±8.26), and 50.2% (n=202) of participants had limited health literacy. Significant associations were observed between health literacy and socio demographic factors, including age (p=0.040), marital status (p=0.009), education level (p=0.03), occupation (p=0.003), monthly income (p=0.001), family type (p=0.025), and family member in a health-related profession (p=0.003). Behavioural factors such as participation in health-related awareness programs (p=0.002), doing a health-related special course (p=0.031), use of the internet for health information (p=0.001), mass media exposure to health-related information (p=0.001), and multilingual capability (p = 0.001) were also significantly associated with health literacy. Conclusion: Half of the respondents had limited health literacy, indicating challenges in accessing, understanding, evaluating, and applying health information necessary for making appropriate health decisions. Targeted health education interventions, multilingual communication, and improved access to digital resources are recommended to enhance health literacy, particularly among low-income and less educated populations.
Keywords: Associated factors; Patients; Health literacy; HLS-EU47 Questionnaire